Charting a low carbon future for shipping: A UK perspective. (August 2017) - Walsh, Conor; Mander, Sarah; Larkin, Alice
Abstract: Projected growth in the international shipping industry is set to outstrip CO2 reductions arising from incremental improvements to technology and operations currently being planned and implemented. Using original scenarios, this paper demonstrates for the first time that it is possible for a nation's shipping to make a fair contribution to meeting global climate change commitments, but that this requires transformation of the sector. The scale and nature of technology change varies depending on the level of demand and how this is satisfied. The scenarios show that to develop successful marine mitigation policy, it is essential to consider the interdependencies between ship speed, level and pattern of demand for services, and the extent and rate of innovation in propulsion technology. Across the scenarios, it is difficult to foresee how deep decarbonisation can be achieved without an immediate, fleet-wide speed reduction; and a land-based energy-system transition strongly influences shipping demand, which in turn, influences the extent of required low-carbon propulsion technology change. Setting the industry on a 2 °C heading requires multifaceted and near-term changes in the shipping sector, but these are unlikely to materialise without a major shift by stakeholders to realise new and innovative deep decarbonisation policies in the coming decade.